Mental Health and Work-Life Harmony among Single Mothers - Nisha Stephen; R Radhika (International Journal of Computer Information Systems and Industrial Management Applications, 2026)
Single mothers frequently have to deal with several aspects of work, child care, household management and financial security, which can be quite demanding emotionally and psychologically. This study explores the mental health and work-life harmony of a single mother and the difficulties she faces in her life as she attempts to balance work and family responsibilities. Mental health is addressed in aspects of emotional health, stress, anxiety, and psychological resilience, while work-life harmony is discussed in the context of role balance, flexibility, satisfaction and the integration of work and family roles. Excessive workload, small social support networks, financial constraints, expectations of work and the lack of time for personal needs were all identified as factors that could have a detrimental effect on the psychological health of single mothers. Meanwhile, positive work policies, flexible working options, childcare support, family support and coping mechanisms may help to improve work-life balance. The study aims to identify what helps boost the well-being of single mothers and make it easier for them to function in all their roles. The results will be used to inform debates about inclusive workplace practices and social support systems for single mothers. The study emphasizes the importance of employers, families, communities, and policy-makers working together and coming to a consensus in promoting mental health and work-life balance.